Active learning in higher education: developing projects in partnership with industry - Dinis-Carvalho, José (2017)
Project Based Learning is an active learning approach with some good results perceived by students, academic staff and employers. A decade of experience and research at the Industrial Management and Engineering (IME) Integrated master programme at the University of Minho has provided strong evidence of its advantages and disadvantages. One of the PBL approaches being applied is based on projects in real contexts, where student teams must analyse and improve aspects of production systems in different companies in the region. The soft skills development as well as the attractiveness of such projects for students are common topics to be explored in such type of initiatives. The objective of this paper is to collect evidence on how such real context projects can be effective in developing specific technical knowledge on students. The technical knowledge covered in this article is based on the curricular unit “Production Systems Organization II” of the 7th semester of the IME programme. Data collection was based on the application of questionnaire to students involved in this semester (n=62). The results show that student perceptions on the effect of the project is, in average, considered “important” (4 in a Likert scale) and that the learning outcomes mostly influenced by the project are related to issues such as the nature of the project and the typology of the company. More complex production systems with complex production flows, high variety of products and more process steps together with more skilled management people, seem to bring better results in student’s understanding of the learning outcomes developed with the project.